Impact of dose‐escalation schemes and drug discontinuation on weight loss outcomes with liraglutide 3.0 mg: A model‐based approach. Issue 6 (19th February 2020) - Papathanasiou, Theodoros; Strathe, Anders; Agersø, Henrik; Lund, Trine Meldgaard; Overgaard, Rune Viig
Abstract: Aims: To investigate the impact on weight loss of the treatment changes in overweight or obese people that may be needed in case of gastrointestinal (GI) tolerability issues during escalation of the glucagon‐like peptide‐1 analogue liraglutide. Materials and methods: The individual longitudinal body weight data from the main trial periods of three phase II/III trials in overweight or obese patients (56‐week treatment with once‐daily liraglutide 1.2, 1.8, 2.4 or 3.0 mg or placebo, n = 4952) were analysed using a non‐linear mixed‐effect modelling approach. Individual pharmacokinetic profiles were derived based on published pharmacokinetic models. Baseline body weight, baseline glycated haemoglobin (HbA1c), age, gender, diabetes status (no diabetes, prediabetes or type 2 diabetes), race and trial region were investigated as covariates. As a form of external validation, the model was used to predict the weight regain after treatment cessation at week 56 (data not included in model development). Results: A pharmacokinetic/pharmacodynamic model provided an adequate description of the weight loss trajectories for all studied doses. Gender and diabetes status were identified as the most influential covariates, and an underlying seasonal weight fluctuation was identified. Slower than that recommended, one‐week dose‐escalation algorithms led up to 2 weeks slower initial weight loss but similar long‐term weight loss trajectories. Conclusions: The relationship between liraglutide systemic exposure and weight loss was successfully established in overweight or obese people. The model could predict the time course of weight regain after treatment cessation and suggests that GI tolerability can be mitigated by slower escalation with only minor impact on the weight loss trajectory.